Addressing Zakat Fragmentation: KMA Priorities for Mandatory Amil Certification for Program Effectiveness. - Nur Rochmawati (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This police paper discusses the low effectiveness of the distribution and utilization of zakat funds in Indonesia despite the large potential for collection. This low effectiveness is identified as originating from three main root problems: Regulatory and Institutional Fragmentation between BAZNAS and LAZ; Limited Human Resource (HR) Capacity in Zakat Management Organizations (OPZ); and Lack of Investment and Standardization in Sustainable Zakat Amil Training. These problems lead to the dominance of charitable programs, low accountability, and the failure of zakat as an instrument for alleviating structural poverty. The writing method uses qualitative policy analysis with a prescriptive approach, referring to the Institutional Theory framework (to analyze fragmentation) and Human Resource Capacity Theory (to analyze amil professionalism). Data were collected through an in-depth literature review of laws and regulations (Law No. 23/2011, KMA), reputable scientific journals with APA 7th citations, and BAZNAS reports. The analysis of alternative policies was conducted using the William N. Dunn Scoring System based on the criteria of Effectiveness, Efficiency, Equity, Responsiveness, and Appropriateness. The analysis results indicate that the highest priority policy alternative is the issuance of a Ministerial Decree (KMA) concerning Competency Standards and Certification for Mandatory Amil. It is recommended that this KMA be issued immediately to fundamentally improve the professionalism of amil, which is key to changing the governance of OPZ and transforming the zakat program from a charitable to a productive approach.